Remote monitoring of atmospheric and hydrophysical characteristics of the water surface based on microwave radiometric measurements - Varotsos, C.A.; Mkrtchyan, F.A.; VY Soldatov (Remote Sensing, 2022)
This work summarizes the main characteristics of atmospheric and hydro-physical parameters of the water surface derived from microwave radiometric data. First, current knowledge based on experimental measurements and model calculations of emissivity of the atmosphere and water surface in the microwave spectrum is presented. Emphasis is placed on remote radio-physical methods that have the peculiarity of being related to atmospheric radio-transparency which is one of the main advantages of the microwave radiometric method compared to optical and infrared methods. A detailed presentation is attempted with specific examples of classification of water surface phenomena using software modules included in the system used for the processing of data of radio-physical experiments by the Cosmos-1500 satellite. In addition, the statistical characteristics of the “spotting” of radio-brightness temperatures obtained for the most informative thresholds are analyzed and it is argued that these characteristics for the Pacific areas can also be used to detect abnormal phenomena on the water surface of the Mediterranean Sea. Finally, it is emphasized that the results obtained from this work make it possible to rapidly evaluate various parameters such as temperature, water surface waves, foam formation areas, etc., providing predictions and allocating irregular areas.